2016
DOI: 10.1002/2016ja022523
|View full text |Cite
|
Sign up to set email alerts
|

The dependence on geomagnetic conditions and solar wind dynamic pressure of the spatial distributions of EMIC waves observed by the Van Allen Probes

Abstract: A statistical examination on the spatial distributions of electromagnetic ion cyclotron (EMIC) waves observed by the Van Allen Probes against varying levels of geomagnetic activity (i.e., AE and SYM‐H) and dynamic pressure has been performed. Measurements taken by the Electric and Magnetic Field Instrument Suite and Integrated Science for the first full magnetic local time (MLT) precession of the Van Allen Probes (September 2012–June 2014) are used to identify over 700 EMIC wave events. Spatial distributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
162
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(199 citation statements)
references
References 63 publications
27
162
2
Order By: Relevance
“…Thus, to some extent, results in this manuscript and those in Saikin et al [] are complementary. In addition, effects of solar wind dynamic pressure are specially checked during isolated preonset in this study, while all EMIC waves observed were categorized by solar wind dynamic pressure data in Saikin et al []. Furthermore, they identify the location of EMIC waves relative to plasmapause according to empirical models, while plasma density data are shown in this manuscript.…”
Section: Summary and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, to some extent, results in this manuscript and those in Saikin et al [] are complementary. In addition, effects of solar wind dynamic pressure are specially checked during isolated preonset in this study, while all EMIC waves observed were categorized by solar wind dynamic pressure data in Saikin et al []. Furthermore, they identify the location of EMIC waves relative to plasmapause according to empirical models, while plasma density data are shown in this manuscript.…”
Section: Summary and Discussionsupporting
confidence: 66%
“…During the 22 geomagnetic storms under research, only 29% of EMIC waves were found in the main phase and the rest in recovery phase. Recently, with observations from Van Allen Probes, the correlation between EMIC wave occurrences in the inner magnetosphere and geomagnetic conditions and solar wind dynamic pressure is checked [ Saikin et al , ], based on their previous work [ Saikin et al , ]. Storm time EMIC waves were more often observed during recovery phase than main phase.…”
Section: Introductionmentioning
confidence: 99%
“…This was initially thought to be a product of the larger geomagnetic storms in October and November of 2012 during which the apogee of the spacecraft was located at ∼7:00 MLT, but the fact that the Van Allen Probes have precessed orbitally to resample this region during their mission and observed similar occurrences implies that this may be a region of significance. Saikin et al [] recorded a similar enhancement of EMIC wave activity observed during geomagnetically quiet periods, which would corroborate our finding of increased pearl pulsation occurrence during quiet periods discussed in section 2.2. The late morning sector at geostationary orbit (just outside of the Van Allen Probe coverage range) has also been shown to be a concentration of azimuthally polarized standing Pc5 waves [ Takahashi and Mcpherron , ; Kokubun , ; Anderson , ], and it has been implied that the late morning and prenoon sectors are most favorable to pearl generation according to the BWP method by Mazur and Potapov [].…”
Section: Observationsmentioning
confidence: 99%
“…In a follow‐up study, Saikin et al . [] examined the geomagnetic condition dependence of EMIC waves. They found as AE index increases the peak of EMIC waves shifted from prenoon to afternoon sector.…”
Section: Introductionmentioning
confidence: 99%